Something We Africans Got. Africa Arts Critical Thought. - Koffi, Anna-Alix; Kouoh, Koyo; Anani, Olivia; Das, Jareh; Gergel, Joseph; Welter, Ana; Gbewonyo, Enam; Djeudji, Janine Gaëlle; Koly, Souleymane; Chalaye, Sylvie; Troly, Agnès; Dechaufour, Pénélope; et al. (Parijs : avril27, 2017)
Whabira, Dana ; Ogunbanwo, Lakin ; Toguo, Barthélémy ; Koly, Souleymane ; Kwahulé, Koffi ; Bruly Bouabré, Frédéric ; Leki Dago, Ananias ; Tadjo, Véronique ; Boni, Tanella ; Angulo Cortes, Liliana ; Van Haver, Raquel ; Biswell, Karen Paulina ; Fanny, Franck ; Kukama, Donna ; Quinonez, Laura ; Rouch, Jean ; Duparc, Henri
boek